Establishing a relationship between semantic clustering and language performance. (31st December 2021) - Mae de la Cruz, Raelynn; Jeffers, Sharlene L; Miller, Justin B; ,
Abstract: Background: Semantic clustering (SC) is an implicit learning strategy commonly utilized on verbal list‐learning tasks. While research has examined SC and executive functioning and memory, little has been done relating SC and language. In the present study, we calculated a SC score on a common list‐learning task and explored relationships with language performance. We predicted weaker SC in individuals with MCI compared cognitively normal individuals, which could potentially be used as an additional measure to help identify MCI and Alzheimer's disease. Method: Archival test data from an outpatient neurology clinic were extracted (N=355), including the Hopkins Verbal Learning Test – Revised, Boston Naming Test, WAIS‐IV Similarities, D‐KEFS Verbal Fluency Letter Fluency (FAS) and Category Fluency (CF) tests, and Wide Range Achievement Test‐Reading (WRAT). Diagnostic subgroups of MCI and CN were created using actuarial diagnostic criteria. SC was calculated as the sum of novel consecutive recalls belonging to the same category, without repeats or semantically‐related intrusions. A chi‐square test was conducted to assess differences between demographic factors. ANCOVA was used to compare performance of SC and selected language measures between the MCI and CN groups using age and WRAT‐Reading as covariates; SC and language measure raw scores were treated as dependent variables and diagnostic grouping as the independent variable. Result: Differences in age( X 2 =36.39, p<0.01), education( X 2 =21.44, p<0.05), and WRAT‐Reading SS( X 2 =45.43, p<0.01) were found. ANOVA found significant differences between the groups' SC scores, as well as performance on language measures (p<0.05). The CN group showed a trend of being stronger than the MCI group across all measures, including SC. Generally, language measures were significantly positively correlated with SC scores for both groups (p<0.05), including BNT and CF, and FAS for the CN group. Conclusion: Overall, findings support our hypothesis that both SC and language scores vary as a function of clinical diagnosis with the CN group having stronger abilities than those with MCI. As such, SC scores derived from verbal learning tests may be able to contribute to knowledge of one's language skills. Further research should aim to help establish this relationship. SC scores could assist in screening for MCI or cognitive deficiencies resulting from AD.